Comparison of accessibility and usability of digital libraries in mobile platforms: blind and visually impaired users’ assessment - Iris Xie; Tae Hee Lee; Hyun Seung Lee; Shengang Wang; Rakesh Babu (Information Research: An International Electronic Journal)
Introduction. This study compares 30 blind and visually impaired users’ assessment of accessibility and usability of the two mobile platforms (mobile app and mobile web) of a digital library.